DETECTION AND ANALYSIS OF CRISPR-CAS SYSTEMS IN PLASMIDS OF DIFFERENT BACILLUS THURINGIENSIS STRAINS - N. A. Arefieva; Yu. P. Dzhioev; L. A. Stepanenko; A. Yu. Borisenko; V. I. Chemerilova; O. F. Vyatchina; O. A. Sekerina; Yu. A. Markova; G. V. Yurinova; V. P. Salovarova; A. A. Pristavka; V. I. Zlobin (Инфекция и иммунитет, 2018)
.